2017
DOI: 10.1111/cdev.12911
|View full text |Cite
|
Sign up to set email alerts
|

Parental Cultural Socialization and Adolescent Private Regard: Exploring Mediating Pathways Through Daily Experiences

Abstract: Using longitudinal experience sampling data from 214 ethnic/racial minority adolescents (Wave 1 M = 15.24), the present study investigated how the longitudinal effect of parental cultural socialization on adolescent private regard was mediated through various daily pathways and novel constructs. Both the mean levels and variability of adolescents' ethnic feelings (i.e., private regard) and social interactions (i.e., intragroup contact) in daily situations, as well as the situational association between intragr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…To facilitate compliance, individualized reminders and encouragements were sent at the end of each day. Comparable to other signal-contingent experience sampling studies (Wang et al, 2017), Muslim American adolescents completed 66% of the surveys on average (56 out of 84 possible surveys per person). In Phase 3, approximately 2 weeks after the experience surveys, adolescents completed a final online survey regarding their civic engagement.…”
Section: Methodsmentioning
confidence: 96%
“…To facilitate compliance, individualized reminders and encouragements were sent at the end of each day. Comparable to other signal-contingent experience sampling studies (Wang et al, 2017), Muslim American adolescents completed 66% of the surveys on average (56 out of 84 possible surveys per person). In Phase 3, approximately 2 weeks after the experience surveys, adolescents completed a final online survey regarding their civic engagement.…”
Section: Methodsmentioning
confidence: 96%
“…Secondly, it was confirmed that very few studies have investigated the influence of parental practices on victimization in schools. Lastly, previous studies have reported a relationship between certain parental practices and the development of social anxiety in adolescents [24,46]. However, as far as we have been able to review, no papers in the scientific literature have analyzed the role of social anxiety in the relationship between parental socialization and school peer victimization.…”
Section: Introductionmentioning
confidence: 91%
“…Previous research has shown the negative consequences that social anxiety has for the life of an adolescent; for example, low acceptance among peers [17,18], a negative perception of the adolescent about himself/herself [19,20], and his/her social skills [21,22]. These consequences, in turn, involve risk factors for adolescent victimization in the school context [23,24]. Indeed, these studies have associated social anxiety with a greater prevalence of this problem in classrooms [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, they found a positive association between cultural socialization and ethnic-racial identity resolution in middle adolescence but not in late adolescence (Douglass and Umaña-Taylor 2016). Another study examined the effect of cultural socialization on children's private regard and found that parental cultural socialization at wave 1 was positively linked to children's ethnic identity at wave 3 and to less variability in situational private regard and intragroup contact at wave 2 (Wang et al 2019). It also found that the co-occurrence of intragroup contact and private regard across situations mediated the link between cultural socialization and children's ethnic identity.…”
Section: Ers and Ethnic-racial Identity Developmentmentioning
confidence: 96%